Elmo2 Is a Regulator of Insulin-dependent Glut4 Membrane Translocation - Sun, Yingmin (J Biol Chem, 2016)
Elmo2, a member of the Elmo protein family, has been implicated in the regulation of Rac1 and Akt activation. Recently, we found that Elmo2 specifically interacts with ClipR-59. Because Akt and Rac1 have been implicated in insulin dependent Glut4 membrane translocation, we hypothesize here that Elmo2 may play a role in insulin-dependent Glut4 membrane translocation. Accordingly, we found that overexpression of Elmo2 enhanced, whereas its knockdown suppressed, insulin-dependent Glut4 membrane translocation in both 3T3-L1 adipocytes and L6 skeletal muscle cells. We also examined whether Elmo2 contributes to the insulin-mediated activation of Rac1 and Akt. We found that Elmo2 is required for insulin-induced Rac1 GTP loading, but not AKT activation, in L6 cells induced by insulin. Instead, Elmo2 is required to promote the insulin-induced membrane association of Akt. Together, our studies demonstrate that Elmo2 is a new regulator of insulin-dependent Glut4 membrane translocation through modulating Rac1 activity and Akt membrane compartmentalization.